Is the Course Working? An Account of Our Development of an Instrument to Measure the Science Attitudes and Skills of Undergraduate Students Outside of Science Disciplines - Ellen Watson; Sheryl Gares; Brian Rempel (Teaching & Learning Inquiry: The ISSOTL Journal)
After a redesign of our school year structure, our science team developed an introduction to science course focused on teaching science to non-science majors early in their post-secondary studies. The goal of this course was not to prepare students for further pursuit of science degrees; instead, we wanted to equip them with the skills and attitudes necessary to understand the scientific world in which we live. Consequently, we wondered whether these skills and attitudes were being met throughout the course; was the course working? When searching the literature, we did not identify any instrument that simultaneously and concisely measured general science skills and attitudes. Given this gap and based on our desire to measure science skills and attitudes for non-science majors at our campus, this research team developed Augustana Interdisciplinary Scientific Literacy Evaluation (AISLE) in order to provide a measurement of students’ science skills and abilities in a general science course at the post-secondary level. However, as we would come to know, this process was not as simple as might seem. The purpose of this paper is to provide an account of the development and validation of the AISLE for those who wish to use the instrument or for others in the SoTL community looking to develop similar tools. We also offer an account of using the AISLE in our course to measure students’ science skill and attitude development. In the end, our STEM-based instructional team learned that what appeared to be straight forward assessment development, was, in fact, a far more involved and complicated process.